Search for Higgs and Z boson decays to J/ψ or Y pairs in the four-muon final state in proton-proton collisions at √s=13 TeV - Sirunyan, A. M. (2019)
A search for decays of the Higgs and Z boson to pairs of J/ψ or Y (nS) (n = 1, 2, 3) mesons, with their subsequent decay to μ+μ- pairs, is presented. The analysis uses data from proton-proton collisions at √s=13 TeV, collected with the CMS detector at the LHC in 2017 and corresponding to an integrated luminosity of 37.5 fb-¹. While an observation of such a decay with this sample would indicate the presence of physics beyond the standard model, no significant excess is observed. Upper limits at 95% confidence level are placed on the branching fractions of these decays. In the J/ψ pair channel, the limits are 1.8 x 10-3 and 2.2 x 10-6 for the Higgs and Z boson, respectively, while in the combined Y (nS) pair channel, the limits are 1.4 x 10-³ and 1.5 x 10-6, respectively, when the mesons from the Higgs and Z boson decay are assumed to be unpolarized. When fully longitudinal and transverse polarizations are considered the limits reduce by about 22–29% and increase by about 10–13%, respectively.